2009
DOI: 10.1371/journal.pone.0008339
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Terminal Differentiation of Hippocampal Granule Neurons and Defective Contextual Memory in PC3/Tis21 Knockout Mice

Abstract: Neurogenesis in the dentate gyrus of the adult hippocampus has been implicated in neural plasticity and memory, but the molecular mechanisms controlling the proliferation and differentiation of newborn neurons and their integration into the synaptic circuitry are still largely unknown. To investigate this issue, we have analyzed the adult hippocampal neurogenesis in a PC3/Tis21-null mouse model. PC3/Tis21 is a transcriptional co-factor endowed with antiproliferative and prodifferentiative properties; indeed, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
110
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(115 citation statements)
references
References 85 publications
4
110
0
1
Order By: Relevance
“…Mouse TIS21 [11] and rat PC3 [12] are homologs of human B-cell translocation gene-2 (BTG2). The data accumulated during the past two decades with both cells and animal models implicate Btg2/TIS21/PC3 (Btg2) in a variety of biological processes such as mediation of stage specific expansion of developing thymocytes [13], regulation of the hematopoietic progenitor cell expansion in response to estradiol [14], cell cycle arrest at G2/M [15] and G1/S phases [16,17], enhancement of cancer cell death via interaction with Pin-1 in response to growth factor stimulation [18] or via accumulation of hydrogen peroxide after doxorubicin treatment [19], and regulation of neuronal differentiation [20,21]. Moreover, Btg2 is involved in the differentiation of myelocytic leukemia cells and CD34 + hematopoietic precursor cells [22,23], DNA repair [24,25], inhibition of cancer cell migration [26], as a transcriptional co-regulator in different model systems, and in the antioxidant defenses through the antioxidant transcription factor NFE2L2 [22,27].…”
Section: Introductionmentioning
confidence: 99%
“…Mouse TIS21 [11] and rat PC3 [12] are homologs of human B-cell translocation gene-2 (BTG2). The data accumulated during the past two decades with both cells and animal models implicate Btg2/TIS21/PC3 (Btg2) in a variety of biological processes such as mediation of stage specific expansion of developing thymocytes [13], regulation of the hematopoietic progenitor cell expansion in response to estradiol [14], cell cycle arrest at G2/M [15] and G1/S phases [16,17], enhancement of cancer cell death via interaction with Pin-1 in response to growth factor stimulation [18] or via accumulation of hydrogen peroxide after doxorubicin treatment [19], and regulation of neuronal differentiation [20,21]. Moreover, Btg2 is involved in the differentiation of myelocytic leukemia cells and CD34 + hematopoietic precursor cells [22,23], DNA repair [24,25], inhibition of cancer cell migration [26], as a transcriptional co-regulator in different model systems, and in the antioxidant defenses through the antioxidant transcription factor NFE2L2 [22,27].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Btg2 expression is significantly upregulated in hematopoietic cells during retinoic acid-induced differentiation [13]. In addition, terminal differentiation of hippocampal granule neurons is severely impaired in Btg2 knockout mice [7]. These results suggest that increased Btg2 expression is positively correlated with development, in particular with terminal differentiation.…”
Section: Introductionmentioning
confidence: 89%
“…Although the exact function of Btg2, a prototype member of the BTG/TOB family, remains unclear, previous studies have implicated Btg2 in a variety of biological events such as embryonic development [6] and terminal differentiation [7]. In addition, Btg2 has been demonstrated to have a role in cell cycle arrest [8] and tumor suppression [9].…”
Section: Introductionmentioning
confidence: 99%
“…BrdU pulse chase studies in Tis21 knockout mice revealed, on one hand, a significant reduction of calbindin-positive mature cells and, on the other hand, a significant increase in DCX þ / calretinin þ immature neurons among 28-d-old newborn cells, suggesting that Tis21 deficiency impaired maturation of adult-generated neurons (Farioli-Vecchioli et al 2009). Krüppel-like factor 9 (Klf9) is a member of the evolutionarily conserved zinc finger transcription factor family.…”
Section: Transcriptional Regulators Of Maturation and Synaptic Integrmentioning
confidence: 99%